Measuring School Climate: Validating the Education Department School Climate Survey in a Sample of Urban Middle and High School Students - Renee Ryberg; Sarah Her; Deborah Temkin; Rebecca Madill; Claire Kelley; Joy Thompson; Alexander Gabriel (AERA Open, 2020)
The U.S. Department of Education’s School Climate Survey (EDSCLS) is a free, open-source school climate survey available for any local or state education agency to use to measure three domains of school climate: engagement, safety, and environment. The present study leverages EDSCLS data from 3,416 students from 26 middle and high schools in Washington, DC to confirm the factor structure of the survey using both single-level and multilevel confirmatory factor analyses. At the individual level, our findings paralleled those from the original validation study conducted by the U.S. Department of Education. At the school level, our findings suggested a simpler factor structure for the engagement and environment domains, and could not identify a reasonable well-fitting model for the safety domain. Particularly, as more states are considering school climate measurement for accountability systems, these findings suggest that simply using the individual-level structure may not yield valid measurement.